Case report: A novel FARS2 deletion and a missense variant in a child with complicated, rapidly progressive spastic paraplegia - Panzeri, Elena; Citterio, Andrea; Martinuzzi, Andrea; Ancona, Vera; Martini, Eleonora; Bassi, Maria Teresa (Frontiers in Genetics, 2023)
Defects in FARS2 are associated with either epileptic phenotypes or a spastic paraplegia subtype known as SPG77. Here, we describe an 8-year-old patient with a severe and complicated spastic paraplegia, carrying a missense variant (p.Pro361Leu) and a novel intragenic deletion in FARS2. Of note, the disease is unexpectedly progressing rapidly and in a biphasic way differently from the previously reported cases. Our study provides the first detailed molecular characterization of a FARS2 deletion and its underlying molecular mechanism and demonstrates the need of combining different tools to improve the diagnostic rate.